Ответ:
Смотри решение.
Объяснение:
[tex]5x(x-4)=(x-8)^2-65\\5x^2-20x=(x^2-16x+64)-65\\5x^2-20x=x^2-16x+64-65\\5x^2-20x=x^2-16x-1\\5x^2-20x-x^2+16x+1=0\\4x^2-4x+1=0\\a=4; b=-4; c=1\\D=b^2-4ac\\D=(-4)^2-4*4*1\\D=16-16\\D=0\\\sqrt{D}=\sqrt{0}=0\\ x_{1}=x_{2}=\frac{-b+\sqrt{D}}{2a}=\frac{4+0}{8}=\frac{4}{8}=\frac{1}{2}=0,5\\[/tex]
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
Смотри решение.
Объяснение:
[tex]5x(x-4)=(x-8)^2-65\\5x^2-20x=(x^2-16x+64)-65\\5x^2-20x=x^2-16x+64-65\\5x^2-20x=x^2-16x-1\\5x^2-20x-x^2+16x+1=0\\4x^2-4x+1=0\\a=4; b=-4; c=1\\D=b^2-4ac\\D=(-4)^2-4*4*1\\D=16-16\\D=0\\\sqrt{D}=\sqrt{0}=0\\ x_{1}=x_{2}=\frac{-b+\sqrt{D}}{2a}=\frac{4+0}{8}=\frac{4}{8}=\frac{1}{2}=0,5\\[/tex]